2011
DOI: 10.1186/2045-8118-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging indicators of blood-brain barrier and brain water changes in young rats with kaolin-induced hydrocephalus

Abstract: BackgroundHydrocephalus is associated with enlargement of cerebral ventricles. We hypothesized that magnetic resonance (MR) imaging parameters known to be influenced by tissue water content would change in parallel with ventricle size in young rats and that changes in blood-brain barrier (BBB) permeability would be detected.MethodsHydrocephalus was induced by injection of kaolin into the cisterna magna of 4-week-old rats, which were studied 1 or 3 weeks later. MR was used to measure longitudinal and transverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
(74 reference statements)
3
17
0
Order By: Relevance
“…9, 11, 12, 23, 24 In DWI studies, hydrocephalus was often found to be associated with abnormally high ADC values in PVWM. 23-25 In DTI studies, lower FA values have been consistently found in the corpus callosum in hydrocephalus, while mixed FA changes have been reported in some other white matter structures, such as the internal capsule. 9-12 …”
Section: Discussionmentioning
confidence: 99%
“…9, 11, 12, 23, 24 In DWI studies, hydrocephalus was often found to be associated with abnormally high ADC values in PVWM. 23-25 In DTI studies, lower FA values have been consistently found in the corpus callosum in hydrocephalus, while mixed FA changes have been reported in some other white matter structures, such as the internal capsule. 9-12 …”
Section: Discussionmentioning
confidence: 99%
“…They show that T1 relaxation time increases with magnetic field while T2 relaxation time decreases (de Graaf et al, 2006, Wright et al, 2008, van de Ven et al, 2007. Some values have been reported in the literature for few brain regions (Barbier et al, 2005, Behroozi et al, 2018, Cremillieux et al, 1998, Del Bigio et al, 2011, Gigliucci et al, 2014, Koundal et al, 2015, Liachenko and Ramu, 2017, Suleymanova et al, 2014, but no consensus has been reached yet about values of reference for specific rat brain regions. To define such reference maps, a large number of brain structures or regions should be considered and a sufficient number of animals should be included to reflect inter-individual variability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans and animals have reported that T 2 values measured in brain tissue using CPMG sequences are dependent on the refocusing interval due to dynamic dephasing caused by the strong magnetic field gradients created by deoxygenated blood in veins and eventual iron/ferritin deposits. Therefore, it is important to keep in mind that the T 2 values reported in the present study correspond to the so‐called apparent T 2 , as defined in . The reported T 2 values can serve as a valid starting point for optimization of the effective echo time of a given RARE sequence.…”
Section: Discussionmentioning
confidence: 99%